Economic Crisis and Healthcare Services - Zavras, Dimitris (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Economic crises, such as the economic crisis of 2008, are related to several issues, including decreases in disposable income and increases in unemployment. At the individual level, decreasing disposable income, unemployment, and loss of insurance coverage have detrimental effects on the ability to seek affordable, quality, and accessible healthcare. At the population level, they have adverse effects on physical and psychological health and on overall well-being. From a healthcare services perspective, economic crises challenge the ability to provide quality, affordable healthcare services that meet the needs and expectations of the population. In the same vein, the economic consequences of the COVID-19 crisis include decreases in income, increases in unemployment, financial uncertainty, declines in living conditions, and pressures exerted on healthcare systems. On the other hand, several non-COVID-19 health-related effects are tied to the pandemic. In this sense, this book attempts to highlight the influences of economic crises on individuals, the world economy, and healthcare. Although the range of challenges attributed to economic crises is quite broad, the collection of articles in this book investigates topics that focus on the global economic crisis of 2008 as well as the one induced by the COVID-19 pandemic. In an environment of negative economic development, these kinds of issues should be highlighted, and potential solutions should be investigated.